Synthesis, Spectral and Thermal Properties of Cu(II) Complex of Schiff Base Derived from Salicylaldehyde and 1,2,3,4-Thiatriazole-5-ylamine - Nath Verma, Upendra; Mukhopadhyay, Kingsuk; Bharti (Asian Journal of Chemistry, 2010)
Schiff base ligand [2-(1,2,3,4-thiatriazole-5-yliminomethyl)-phenol] (L) was synthesized by condensation reaction of 1,2,3,4-thiatriazole-5-ylamine and salicylaldehyde. 1,2,3,4-Thiatriazole- 5-ylamine is derived from thiosemicarbazide. The synthesized ligand was found to be potential ligand towards transition metal ions. The reaction of copper(II) salt with Schiff base ligand (L) resulted in the formation of a solid complex [Cu(II)(L)2]·2H2O. The ligand and the complex were characterized through elemental analysis, IR, UV-vis and 1H NMR spectroscopies. The thermal property of the complex was studied by thermogravimetric analysis.